PRODUKSI BEBERAPA VARIETAS TEMBAKAU LOKAL PADA TANAH REGOSOL DI KABUPATEN GARUT - Meksy Dianawati; Kiki Kusyaeri Hamdani (Universitas Trilogi, 2022)
This study aims to determine the production of several local tobacco varieties on regosol soil in Garut Regency. The study was conducted in Sukakarya Village, Samarang District, Garut Regency, West Java Province from April to August 2017. The study used a Randomized Complete Block Design (RCBD) with 4 varieties and 6 replications. The local varieties used are Kedu Hijau, Kedu Omas, Kedu Nani, and Kenceh. Data were analyzed by F test and continued with Duncan's Test and Correlation Test at 95% confidence level. The results showed that the production of local tobacco varieties that were resistant to bacterial wilt (Kedu Hijau and Kedu Omas) was higher than that of varieties that were susceptible to bacterial wilt (Kedu Nani and Kenceh). Narrow-leaved bacterial wilt-susceptible varieties had higher yields than broad-leaved varieties, while broad-leaved bacterial wilt-resistant varieties had higher yields than narrow-leaved varieties. Production was influenced by leaf weight, leaf thickness, and leaf length by 92%, 89% and 53%, respectively.